Outlining a Model of an Intelligent Decision Support System Based on Multi Agents - Benmoussa, N.; Fakhouri Amr, M.; Ahriz, S.; Mansouri, K.; Illoussamen, E. (Engineering, Technology & Applied Science Research, 2018)
Performance optimization has become a necessity for the survival of enterprises as emerging technologies continue to impact them. To achieve this goal, decision making, a complex process which depends on big data and human issues, must be effective. As enterprises are being subjected to a multi-faceted pressure, they must ensure the optimization of their performance. This article investigates an intelligent decision support system (IDSS) based on multi agent systems (MAS). Our contribution consists in developing an intelligent model with an IDSS MAS approach that can detect and evaluate changes in both the external environment and the enterprise itself. This model is an adequate management tool for optimal and sustainable performance and offers real-time analytical, prospecting and optimization methods.